2022
DOI: 10.3389/fmed.2022.763833
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution Pattern of Ocular Residual Astigmatism in Chinese Myopic Patients

Abstract: PurposeWe aimed to investigate the distribution of ocular residual astigmatism (ORA) and its associations with age, gender, manifest refraction, and other ocular indicators in Chinese patients with myopia.DesignThis is a multi-center retrospective cross-sectional study.MethodThe study included 7,893 patients with myopia (7,893 eyes) aged 18–40 years from five ophthalmic centers. Anterior segment biometrics of the eyes were collected from the Pentacam. ORA and its summated vector mean were calculated using Alpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Yuta Ueno and associates found that the difference between horizontal and vertical corneal thickness was correlated with the posterior corneal astigmatism ( 32 ), Zhou X etc., discovered that the front and back curvatures and the back astigmatism correlate with the distribution of corneal thickness ( 33 ). In addition, we also found that myopia is associated with increased astigmatism, which was also found in a large German population-based study ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…Yuta Ueno and associates found that the difference between horizontal and vertical corneal thickness was correlated with the posterior corneal astigmatism ( 32 ), Zhou X etc., discovered that the front and back curvatures and the back astigmatism correlate with the distribution of corneal thickness ( 33 ). In addition, we also found that myopia is associated with increased astigmatism, which was also found in a large German population-based study ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
“…It was approved by the Institutional Review Board (IRB) of Guangzhou Aier Eye Hospital (GZ), Shenyang Aier Eye Hospital (SY), Wuhan Aier Eye Hospital (WH), Chengdu Aier Eye Hospital (CD) and Hankou Aier Eye Hospital (HK) and conducted according to the tenets of the Declaration of Helsinki. Our study was only a review of medical records from which patients could not be identified, so the IRBs decided to waive the requirement to get informed consent 25–27 . We reviewed the digital medical records of myopic patients who had refractive surgery between 2017 and 2020 in the five centers.…”
Section: Methodsmentioning
confidence: 99%
“…Only the right eye of the participants was included in the analysis. Exclusion criteria were patients wearing soft contact lenses within 2 weeks or rigid gas‐permeable lenses within 1 month before the Pentacam examination, and those with eye diseases (glaucoma, trauma, previous ocular surgery, keratoconus or suspected keratoconus severe dry eye, corneal degeneration, or dystrophy) 25,26 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations